IMPROVING CREATIVITY AND LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS BY IMPLEMENTING PROBLEM BASED LEARNING AND YOUTUBE - Noviana Rohmatin; Suwarto Suwarto; Anwari Adi Nugroho (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This study aims to increase creativity and learning outcomes of biology in class X MIPA State Senior High School with problem-based learning model in biology learning. This research is classroom action research carried out in 3 cycles, each cycle consisting of 4 stages; planning, implementing actions, observing, and reflecting. The subjects of this research were 36 students. The data in this study are creativity and student learning outcomes. Creativity data is measured by Mind Mapping observation sheets and cognitive learning outcomes data is measured by test questions at the end of each cycle, affective learning outcomes are measured by attitude assessment observation sheets, psychomotor learning outcomes are measured by skills observation sheets. Data on creativity and cognitive, affective and psychomotor learning outcomes were analyzed using the percentage technique and then described comparatively for each cycle. The results showed that there was an increase in creativity in the first cycle of 42%, the second cycle 55% and the third cycle 78%. While cognitive learning outcomes in cycle I 66%, cycle II 72% and cycle III 88%, affective learning outcomes in cycle I 41%, cycle II 63% and cycle III 74%, psychomotor learning outcomes in cycle I 36%, cycle II 50 %, cycle III 69%. The research data shows that the application of the Problem Based Learning model with YouTube can improve creativity and student learning outcomes. The increase in creativity occurred in cycle I to cycle II 13%, cycle II to cycle III 23%. Cognitive learning outcomes from cycle I to cycle II 6%, cycle II to cycle III 16%, affective learning outcomes from cycle I to cycle II 22%, cycle II to cycle III 11%, psychomotor learning outcomes from cycle I to cycle II 14 %, cycle II to cycle III 19%. PBL activities such as dealing with problems, analyzing and solving problems so as to make students creative in compiling works in the form of Mind Mapping and increasing cognitive, affective and psychomotor learning outcomes.